2008
DOI: 10.1108/13665620810871105
|View full text |Cite
|
Sign up to set email alerts
|

An integrative model of organizational learning and social capital on effective knowledge transfer and perceived organizational performance

Abstract: Purpose -The purpose of this paper is to set out to examine the relationships of organizational learning, social capital and the effectiveness of knowledge transfer and perceived organisational performance. Integrating organizational learning capability with social capital networks to shape a holistic knowledge sharing and management enterprise framework is a significant strategy to achieve organizational success. Design/methodology/approach -An integrative framework is used to determine the relationships of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 44 publications
4
72
0
7
Order By: Relevance
“…Several recent quantitative studies (e. g., Barba-Aragon et al, 2014;Caps and Lna-Aroca, 2012;Rhodes et al, 2008) have found direct as well as indirect positive association between organisational learning and firm performance. We thus develop the following hypotheses:…”
Section: Organisational Learning and Firm Performancementioning
confidence: 97%
“…Several recent quantitative studies (e. g., Barba-Aragon et al, 2014;Caps and Lna-Aroca, 2012;Rhodes et al, 2008) have found direct as well as indirect positive association between organisational learning and firm performance. We thus develop the following hypotheses:…”
Section: Organisational Learning and Firm Performancementioning
confidence: 97%
“…It is observed that companies increasingly rely on external sources of knowledge to extend their knowledge assets to foster innovation and enhance performance (Haider, 2003;Lichtenthaler, 2009). Today, it is indisputable that a firm's ability to learn faster than its competitors is the only form of sustainable competitive advantage that entities of an entrepreneurial orientation have: and by focusing on being innovative and emphasising organisational learning as a way to discover something new that can bring added value, it allows them to strengthen their competitiveness (de Geus, 1988;Davenport & Prusak, 2000;Rhodes et al, 2008). Certainly, a company has a choice -it may create necessary knowledge itself (e.g.…”
Section: Organizational Learningmentioning
confidence: 99%
“…Barlow & Jashapara, 1998;Zahra & George, 2002;Adams & Lamont, 2003;Rhodes, Lok, Yu-Yuan Hung & Fang, 2008;Beyer, 2011), in the contemporary competitive business environment the ability to learn becomes the priority of any ambitious company. Today, there is no doubt that the challenges of business reality require constant development of a firm's ability to integrate different kinds of knowledge, and to coordinate its usage, leading to valuable commercial outcomes (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava et al, (2008) argue that the organization that effectively meets the expectations of all stakeholders is an excellent organization. Customer focus and satisfaction is also viewed as primary determinant of performance excellence (Day, 2003) and a key performance indicator in many frameworks, such as the balanced scorecard framework (Rhodes et al, 2008), Skandia Navigator (Skandia, 1994), etc. Therefore, tools with a customer orientation should receive the greatest attention (Frazier & Swiss, 2008) to develop deeper knowledge-enabled relationships (Riege, 2005;Schotte, 2003).…”
Section: Sharing Strategies and Customer Focus As An Organizational Ementioning
confidence: 99%